anaerobic load and its effect on the aerobic quality through small-sided soccer games a case study on tadjenanet team for the 2019/2020 sports season - Amra , zakaria (sports creativity, 2025)
The study aimed to determine the effect of anaerobic load on improving the aerobic aspect using small-sided games during preparation phase according to play position. The study was conducted on a sample of 24 players, out of a total of 375 players active in the second professional League at the level of 15 teams and was completed Selecting it intentionally. The researcher followed the experimental approach by applying the Small-sided games, where the vma pre-test was apllied and then the small-sided games programme was applied, immediately afterwards the vma test was retested. After the statistical treatment, the results indicated a statistically significant differences between the pretest and the post test for the group and according to the play position, thus the application of the small-sided games characterized by anaerobic load has an effect on improving the aerobic qualit